Alginate hydrogel cross-linked by Ca2+ to promote spinal cord neural stem/progenitor cell differentiation and functional recovery after a spinal cord injuryhh. (18th August 2022) - Zhou, Jun; Wu, Yaqi; Tang, Zhijian; Zou, Kaipeng; Chen, Juan; Lei, Zuowei; Wan, Xueyan; Liu, Yanchao; Zhang, Huaqiu; Wang, Yu; Blesch, Armin; Lei, Ting; et al.
Abstract: Alginate capillary hydrogels seeded with differentiated cells can fill the lesion cavity and promote axonal regeneration after grafting into the injured spinal cord. Neural stem/progenitor cells (NSPCs) can potentially repair the spinal cord; however, effects of alginate hydrogels (AHs) on NSPCs remain unknown. In this study, we fabricated AHs cross-linked by Ca 2+ and seeded hydrogels with rat embryonic day 14 NSPCs. Immunocytochemistry and electron microscopy show that NSPCs survive, proliferate and differentiate into neurons in vitro within the capillaries. After transplantation into an acute T8 complete spinal cord transection site in adult rats, approximately one-third (38.3%) of grafted cells survive and differentiate into neurons (40.7%), astrocytes (26.6%) and oligodendrocytes (28.4%) at 8 weeks post-grafting. NSPCs promote the growth of host axons within the capillaries in a time-dependent manner. Host axons make synapse-like contacts with NSPC-derived neurons within the hydrogel channels, and graft-derived axons extend into the host white and gray matter making putative synapses. This is paralleled by improved electrophysiological conductivity across the lesion and partial hindlimb locomotor recovery. Graphical Abstract: